Carbides and possible hydrogen irreversible trapping sites in ultrahigh strength round steel. (December 2017) - Cheng, X.Y.; Li, H.; Cheng, X.B.
Highlights: Two kinds of carbides are found in the investigated ultrahigh strength round steel. These two types of carbides are iron carbide M6 C and niobium carbide MC. We firstly find that M6 C is not the irreversible trapping sites for H but MC is. H contents in carbides need to be corrected due to different evaporation field. Abstract: The carbides in ultrahigh strength round steel have been investigated by using laser-assisted atom probe tomography (APT) and high resolution transmission electron microscopy (HRTEM) in this paper. Two kinds of carbides are found and one is iron carbide M6 C, where carbide formation elements Cr, Mn and Mo replace partial Fe, while the other is niobium carbide MC, where M includes V and Mo besides Nb. These two carbides, due to their different evaporation field, have various densities in reconstructed image of APT. After correction, the hydrogen content within these two carbides illustrates that M6 C cannot trap hydrogen, while MC can. The different behaviors in trapping hydrogen between these two carbides may result from elements Fe or Cr in M6 C carbide having weaker affinity for hydrogen than Nb and V have in MC.